Continuous Use of Combined Hormonal Contraceptive and the Effect on Blood Coagulation Factors in Female Capuchin Monkeys (Sapajus libidinosus) - Rosângela C. Rodrigues; Flávia Schechtman Belham; Ana Garcia; Corina Satler; Carlos Tomaz; Maria Clotilde H. Tavares (International Journal of Endocrinology)
This study aimed at evaluating the availability of the primate Sapajus libidinosus as an animal model for research assessing the physiological effects of the continuous use of combined hormonal contraceptives. In order to do this, six reproductively active female S. libidinosus from the Primate Research Center of the University of Brasília were selected to take part in this experiment. Every 21 days or so, each female received a single dose of combined hormonal contraceptive (algestone acetophenide and 17-enanthate estradiol) in a total of five doses throughout the experiment. The physiological parameters were accessed by means of 13 blood samples from each female, whereas three were gathered during the baseline and 10 samples were collected during the treatment phase. The results showed that the contraceptive use provoked changes in hematological coagulation factors such as an increase in the amount of platelets (p=0.039) and a reduction in both prothrombin (p<0.001) and thromboplastin coagulation time (p<0.001). These results are similar to what has been observed in human patients; thus, it is concluded that S. libidinosus can be successfully used in studies about the physiological impact of hormonal contraceptives.